Dispersion in Dispersion: Measuring Establishment-Level Differences In Productivity - Cindy Cunningham; Lucia Foster; Cheryl Grim; John C. Haltiwanger; Sabrina Wulff Pabilonia; Jay Stewart; Zoltan Wolf (Institute of Labor Economics (IZA), 2021)
We describe new experimental productivity statistics, Dispersion Statistics on Productivity (DiSP), jointly developed and published by the Bureau of Labor Statistics (BLS) and the Census Bureau. Official BLS productivity statistics provide information on aggregate productivity growth. Yet, a large body of research shows that within-industry variation in productivity provides important insights into productivity dynamics. This research reveals large and persistent productivity differences across businesses, even within narrowly defined industries. These differences vary by industry and time and are related to productivityenhancing reallocation. Dispersion in productivity across businesses can provide information about the nature of competition and frictions within sectors, and about the sources of rising wage inequality across businesses. Because there were no official statistics providing this level of detail, BLS and the Census Bureau partnered to create measures of within-industry productivity dispersion. These measures complement official BLS aggregate industry-level productivity growth statistics and thereby improve our understanding of the rich productivity dynamics in the U.S. economy. The microdata underlying DiSP are available for use by qualified researchers on approved projects in the Federal Statistical Research Data Center network. DiSP confirms the presence of large productivity differences, and we hope that it will encourage further research into understanding these differences.
Keywords: D24; E24; E32; 330; manufacturing; reallocation; within-industry variation; establishments; business cycles